Enhanced Primary Care improves GP service regularity in older patients without impacting on service frequency - Gibson, D.; Moorin, Rachael; Preen, D.; Emery, J.; Holman, C. (The Australian Journal of Primary Health, La Trobe University, 2012)
The objective of this study was to assess the impact of Enhanced Primary Care service utilisation on subsequent GP service regularity and frequency. The study involved a retrospective population-based longitudinal cohort using linked administrative health records of hospital and primary care services for people over the age of 65 years. Multinomial logistic regression modelling was used to evaluate changes in the relative likelihood of increased primary care service regularity and frequency in exposed and unexposed individuals adjusting for age, sex and recent chronic disease hospitalisation history. Enhanced Primary Care services significantly and substantially increased the relative likelihood of increased regularity with no corresponding higher likelihood of increased frequency of GP contact. Increased regularity was more likely with increasing age except for the oldest age group (90+ years). Some chronic disease histories (e.g. diabetes) showed a higher likelihood of improved regularity while others were less likely to produce an increased regularity (e.g. hypertension). The study suggests a capacity for modification of physician and patient behaviour using incentivised services within the current fee-for-service system in Australia.